2015
DOI: 10.1378/chest.14-0960
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Genotyping of Mycobacterium tuberculosis Isolated From Water and Soil Samples of a Metropolitan City

Abstract: BACKGROUND:Th e potential role of environmental Mycobacterium tuberculosis in the epidemiology of TB remains unknown. We investigated the transmission of M tuberculosis from humans to the environment and the possible transmission of M tuberculosis from the environment to humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 23 publications
(20 reference statements)
0
36
0
Order By: Relevance
“…The LAM genotype (3%) was found in our study with a unique spoligopattern (ST 33). LAM was also isolated from water samples in Iran [39], suggesting that it might be transmitted across the border between the two countries. The LAM genotype is relatively rare in Pakistan, but a few cases have been reported from the Sindh province [19], which shares a border with Balochistan.…”
Section: Discussionmentioning
confidence: 99%
“…The LAM genotype (3%) was found in our study with a unique spoligopattern (ST 33). LAM was also isolated from water samples in Iran [39], suggesting that it might be transmitted across the border between the two countries. The LAM genotype is relatively rare in Pakistan, but a few cases have been reported from the Sindh province [19], which shares a border with Balochistan.…”
Section: Discussionmentioning
confidence: 99%
“…13 M. tuberculosis has been detected in stool specimens of individuals with active TB, 20 and in soil and wastewater in high TB burden areas. 21 M. tuberculosis transmission from medical waste 22 and aerosolization from wound irrigation 23 has been documented. While it is possible that M. tuberculosis aerosolization via flush toilets could occur, 24 it is likely that flush toilet use may be a proxy for some unmeasured factor associated with acquisition of M. tuberculosis infection.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of CHEST (see page 1094), Velayati et al 1 reported the surprising finding of viable M tuberculosis in 10% of water samples (and 1% of soil samples) in metropolitan Tehran.…”
Section: To the Editormentioning
confidence: 99%
“…The elegant studies that showed that M tuberculosis can be spread by aerosolized droplet nuclei did not exclude transmission through other routes. The findings of Velayati et al 1 suggest that a broader view of possible routes of TB transmission should be reconsidered. Furthermore, immunologic effects of oral exposure to environmental sources of M tuberculosis , whether associated with infection and disease, merit consideration.…”
Section: To the Editormentioning
confidence: 99%